Pengenalan Proses Gugatan Dalam Hukum Acara Perdata - Oktavia, Lia (Media Hukum Indonesia (MHI), 2024)
This article discusses the lawsuit process in civil procedural law which is an integral part of the justice system in Indonesia. This process includes stages that the plaintiff must go through, starting from filing a lawsuit, providing evidence, to a court decision. Each stage has regular procedures and is regulated by applicable legal provisions, which aim to provide legal protection for individual rights in a civil context. This article also reviews various legal aspects related to filing a lawsuit, the parties involved, and the rights and obligations of each party during the judicial process. With a good understanding of this process, it is hoped that a fair, transparent and efficient judiciary can be created in resolving civil disputes.